AB0006 Genetic Susceptibility Variants for Rheumatoid Arthritis do not Associate with Radiological Progression in Early Active Disease. (10th June 2014) - Scott, I.C.; Walker, J.; Quist, J.; Spain, S.L.; Tan, R.; Steer, S.; Okada, Y.; Raychaudhuri, S.; Cope, A.P.; Lewis, C.M.
Abstract : Background: Several studies have tested the hypothesis that RA susceptibility variants associate with radiological progression. Their findings are often not replicated; additionally they have examined only a proportion of risk loci and evaluated each locus separately, despite limited power. Two recent meta-analyses of genome-wide association studies have expanded the number of genetic loci and HLA amino acid polymorphisms associated with RA susceptibility [1, 2]. Our aim was to establish if these variants correlated with radiological progression in early active RA patients enrolled to a clinical trial. We evaluated their association both individually and cumulatively, using a weighted genetic risk score (wGRS) combining risk loci. Objectives: To establish if genetic predictors of RA susceptibility also associate with radiological progression in early active RA. Methods: We evaluated 421 RA patients previously enrolled to the Combination Anti-Rheumatic Drugs in Early RA (CARDERA) trial. Hand/feet radiographs were read for modified Larsen scores every 6 months for 2 years. We evaluated the association of validated genetic risk variants (69 SNPs, 17 four-digit HLA-DRB1 alleles and polymorphisms in 6 HLA amino acid positions) with log-transformed Larsen scores over time using a linear mixed-effects model. Loge (Larsen score + 1) was the response variable. Time, treatment, age, disease duration, ACPA status, genotype and a genotype*time interaction, were the fixed-effects predictor variables. Genotype was coded additively. All β-estimates were back-transformed to the original Larsen scale. The genotype*time β provided information on the annual increase in Larsen score per risk allele copy relative to the reference genotype; P -values for this term provided information on the variant's role in radiological progression. We assessed the association between a wGRS incorporating susceptibility SNPs and radiological progression by replacing the linear model's genotype term with a wGRS. Ethical approval was obtained; all patients provided consent. Results: Two SNPs, one HLA-DRB1 allele and two HLA-DRβ1 protein amino acid polymorphisms had P -values <0.05 (Table). None attained Bonferroni corrected significance. No association was seen between a wGRS and Larsen score progression ( P =0.0680). Conclusions: RA susceptibility loci did not have a clinically relevant association with radiological progression in European ancestry, early, active RA patients recruited to this trial. This suggests the genetic architectures of RA susceptibility and severity differ. References: Okada Y et al. Genetics of rheumatoid arthritis contributes to biology and drug discovery. Nature 2013; [Epub ahead of print]. Raychaudhuri S et al. Five amino acids in three HLA proteins explain most of the association between MHC and seropositive rheumatoid arthritis. Nat Genet 2012;44:291-6. Acknowledgements: Arthritis Research UK (Grant Reference Number 19739 to ICS); National Institute for Health Research (NIHR) Biomedical Research Centre at Guy's and St Thomas' NHS Foundation Trust in partnership with King's College London. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5018